Effect of nicorandil, on blood glucose level in alloxan induced diabetic rats and its pharmacodynamic interaction with glibenclamide - ., Soni (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Diabetes increases the risk of macrovascular complications and is often associated with angina in patient. Currently nicorandil, a potassium channel opener is being frequently used for the prevention and long-term treatment of angina pectoris. Glibenclamide exerts its antidiabetic action by closing the ATP sensitive potassium channels. Simultaneous use of nicorandil may antagonizes this action and may worsens the existing diabetes. To evaluate the pharmacodynamic interaction present study has been taken to study the effect of Nicorandil, a potassium channel opener on blood glucose level of alloxan induced diabetic rats and its pharmacodynamics interaction with Glibenclamide. Methods: Albino rats, weighing 150-200gm of male sex were used for the study. Diabetes was induced by injecting alloxan monohydrate 2% solution intra peritoneally in a dose of 150mg/kg body weight. Animal with Fasting Blood Sugar level between 250-300g/dl was selected for study and they were divided into 4 groups of 5 animals each. Group I- serving as control received 0.5ml normal saline orally for 28 days. Group II was given glibenclamide (0.5mg/kg body wt) for 28 days. Group III was treated orally with nicorandil (0.3mg/kg body wt) for 28 days. Group IV was given glibenclamide (0.5mg/kg) and nicorandil (0.3mg/kg) for 28 days. Fasting Blood Sugar level was recorded in all rats on 1st,3rd,7th,14th,21st and 28th day of the treatments. Results: results showed that glibenclamide significantly reduce blood sugar level (p <0.05) Wherase nicorandil showed rise in blood glucose level (p <0.05) While the combination (glibenclamide + nicorandil) showed rise in blood glucose (p <0.05) overall. Conclusions: Nicorandil worsen the existing diabetes and to be avoided or replaced with alternative drug in case of diabetes being treated with sulfonyl urease group of drugs.